(untitled) (Asian Journal of Ethnobiology, 2021)
Abstract. Novriyanti N, Nursanti N, Wulan C. 2021. Short Communication: Do women have a piece of traditional knowledge of medicinal plants? A case study around Jambi Urban Forest, Indonesia. Asian J Ethnobiol 4: 115-119. Gender, especially women, significantly affect knowledge, especially maintaining knowledge and practice of medicinal plants. But the question, also will be the research aims is, do they know medicinal plants and grow them themselves in their yards? Data was collected using open and closed interviews with families, including the village shamans. The results showed half of the women around Urban Forest know traditional medicinal plants. Women use 27 plants species to protect and heal their families from minor ailments. Some of the plants found around Urban Forest also plant in their yards; unfortunately, the number of traditional medicinal plant users decreases over time.